Cognitive Recovery During Inpatient Rehabilitation Following Pediatric Traumatic Brain Injury: A Pediatric Brain Injury Consortium Study. Issue 4 (July 2021) - Watson, William D.; Suskauer, Stacy J.; Askin, Gulce; Nowak, Sophie; Baum, Katherine T.; Gerber, Linda M.; Blackwell, Laura S.; Koterba, Christine H.; Hoskinson, Kristen R.; Kurowski, Brad G.; Mclaughlin, Matthew J.; Tlustos, Sarah J.; et al.
Abstract : Objectives: To characterize the demographics, clinical course, and predictors of cognitive recovery among children and young adults receiving inpatient rehabilitation following pediatric traumatic brain injury (TBI). Design: Retrospective observational, multicenter study. Setting: Eight acute pediatric inpatient rehabilitation facilities in the United States with specialized programs for treating patients with TBI. Participants: Children and young adults (0-21 years) with TBI (n = 234) receiving inpatient rehabilitation. Interventions: Not applicable. Main Outcome Measures: Admission and discharge status assessed by the WeeFIM Cognitive Developmental Functional Quotient (DFQ) and Cognitive and Linguistic Scale (CALS). Results: Patients admitted to pediatric inpatient rehabilitation are diverse in cognitive functioning. While the majority of patients make improvements, cognitive recovery is constrained for those admitted with the most severe cognitive impairments. Age, time since injury to rehabilitation admission, and admission WeeFIM Cognitive DFQ are significant predictors of cognitive functioning at discharge from inpatient rehabilitation. Conclusions: This work establishes a multicenter Pediatric Brain Injury Consortium and characterized the demographics and clinical course of cognitive recovery during inpatient rehabilitation of pediatric patients with TBI to aid in prospective study design. Abstract : Supplemental Digital Content is Available in the Text.